2012
DOI: 10.1128/aac.05454-11
|View full text |Cite
|
Sign up to set email alerts
|

Baseline In Vitro Activities of the Antimalarials Pyronaridine and Methylene Blue against Plasmodium falciparum Isolates from Kenya

Abstract: We have analyzed the in vitro activities of pyronaridine and methylene blue against 59 Plasmodium falciparum isolates from Kenya in association with polymorphisms in Pfcrt (codon 76), Pfmdr1 (codon 86), and Pfnhe (full sequence). The median inhibitory concentrations that kill 50% of parasites were 13.5 and 3.3 nM for pyronaridine and methylene blue, respectively. Their activities were not associated with polymorphisms in these genes. The drugs' high in vitro activities indicate that they would be efficacious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…This result is similar to previous studies conducted in Thailand 30 years ago and elsewhere at the present time. 16,29,35,36,[38][39][40][41][42][43] The clear standard cut-off point of pyronaridine is still unavailable. A related study suggested estimating using the geometric mean plus 2 SDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is similar to previous studies conducted in Thailand 30 years ago and elsewhere at the present time. 16,29,35,36,[38][39][40][41][42][43] The clear standard cut-off point of pyronaridine is still unavailable. A related study suggested estimating using the geometric mean plus 2 SDs.…”
Section: Discussionmentioning
confidence: 99%
“…Pyronaridine IC 50 was also positively correlated with artesunate IC 50 which is similar to two related studies. 29,41 However, a statistically significant result (P < 0.05) can often be seen when comparing the drug activities against a large number of isolates. The r value > 0.7-0.8 or r 2 value > 0.5 is more suggestive of cross-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Quinacrine is an old antimalarial drug now more widely used as an antiprotozoal for the treatment of giardiasis 66 and as an anthelmintic. Pyronaridine is a potent antimalarial (IC 50 13.5 nM) 67 , has activity against Babesi a spp. 68 , is active in vitro (EC 50 225 nM) and in vivo (85.2% efficacy 4 days treatment at 50 mg/kg) against T. cruzi 30 and is a P-glycoprotein inhibitor 69 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies indicate potent activity against recent isolates of multidrug-resistant strains of both P. falciparum and P. vivax from Papua, Indonesia [26], against Kenyan P. falciparum isolates [27], and against around half of chloroquine-resistant P. falciparum strains from the China–Myanmar border area [28]. The PA clinical development programme included two Phase II trials and three Phase III trials in children and adults from Africa and Asia with uncomplicated P. falciparum malaria [15,22,24,25], as well as one comparative Phase III trial in children and adults with uncomplicated P. vivax infection [23].…”
Section: Introductionmentioning
confidence: 99%